(untitled) (Journal of Social Sciences Review, 2023)
In recent decades, there is a significant increase in divorce rates throughout the world and particularly in poor and developing countries like Pakistan. In Pakistani society due to patriarchy, socio-cultural and religious reasons divorce is considered a taboo, which creates many long-lasting distresses for women in their social adjustment after the divorce. Therefore, the Social adjustment of divorced women is a social problem that raises many social and cultural questions in Pakistani society. The study is an attempt to find out the causes of divorce and to explore the social adjustment of divorced women in Pakistani society. Moreover, the influence of divorce on the personal lives of women and families is also comprehended. For this exploratory research snowball, a sampling technique is used to approach the respondents. In-depth interviews are conducted to collect the data. The thematic analysis is used to explore the phenomena. This research provides valuable insights into the reasons for divorce and the challenges faced by divorced women in their social adjustment in Pakistan. The research highlights the importance of societal support, acceptance and the socio-economic factors leading to divorce. Addressing the mentioned factors can promote healthier relationships and well-being among families.